2021
DOI: 10.1609/aaai.v35i10.17066
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised Medical Image Segmentation through Dual-task Consistency

Abstract: Deep learning-based semi-supervised learning (SSL) algorithms have led to promising results in medical images segmentation and can alleviate doctors' expensive annotations by leveraging unlabeled data. However, most of the existing SSL algorithms in literature tend to regularize the model training by perturbing networks and/or data. Observing that multi/dual-task learning attends to various levels of information which have inherent prediction perturbation, we ask the question in this work: can we explicitl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(106 citation statements)
references
References 42 publications
0
106
0
Order By: Relevance
“…When using the MSD dataset as the source domain, the performance of pretrained model directly testing on the NIH dataset yielded 69.46%, while the results after proposed adaptation could achieve 77.13% (with a gain of 7.67%). Luo et al 47 . proposed a semisupervised segmentation method using a portion of labeled data from NIH dataset to train the segmentation model and obtained a DSC score of 78.27%.…”
Section: Resultsmentioning
confidence: 99%
“…When using the MSD dataset as the source domain, the performance of pretrained model directly testing on the NIH dataset yielded 69.46%, while the results after proposed adaptation could achieve 77.13% (with a gain of 7.67%). Luo et al 47 . proposed a semisupervised segmentation method using a portion of labeled data from NIH dataset to train the segmentation model and obtained a DSC score of 78.27%.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fagherazzi, et al [ 137 ] presented a semi-supervised clustering technique for healthcare data, while Yu, et al [ 138 ] suggested a semi-supervised ML strategy for activity detection using sensor data. Peng, et al [ 139 ] and Luo, et al [ 140 ] used a semi-supervised learning strategy to segment medical images.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Adversarial learningbased methods [15] use discriminators to encourage the predictions of unannotated images to be similar to those of the annotated ones, where prior information [18] may be used to improve the performance. Consistency regularization methods encourage predictions from one input image under different perturbations to be consistent, e.g., transformation consistency [19], dual-task consistency [20], and perturbationbased consistency [21].…”
Section: A Semi-supervised Learningmentioning
confidence: 99%